2002
DOI: 10.1046/j.1365-2273.2002.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone resorption after alloplastic augmentation of the mandible

Abstract: Augmentation mentoplasty is a commonly performed operation especially in conjunction with rhinoplasty. While various materials have previously been used for this procedure, silastic has been the implant of choice for the last three decades. Concerns have been raised due to the occurrence of bone resorption beneath these implants. Controversy prevails as to the cause and the long-term effects of the resorption. It has been suggested by some that the resorption is self-limiting although this has not been confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Alloplastic material can cause massive bone resorption due to pressure on the adjacent implant-bearing bone 11,12,14,17 , while autologous bone is replaced with newly formed vital bone within a short time 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Alloplastic material can cause massive bone resorption due to pressure on the adjacent implant-bearing bone 11,12,14,17 , while autologous bone is replaced with newly formed vital bone within a short time 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The silicon does not present osseous integration, and may even cause bone resorption as a radiological study that assessed their location and method of implantation 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients included ranged in each study from 2 to 601 patients, for a total of 1,051 patients. The total number of patients who had fixated implants was 799 (76.02%) [11,12,15,16], and 252 patients (23.97%) had nonfixated implants [8,9,14,[17][18][19][20]. The number of implants based on implant site was 933 in the chin (81.05%) [9,12,[14][15][16][17][18][19][20], 160 in the malar region (13.90%) [8,16], and 58 (5.03%) as angle implants [11].…”
Section: Reviewmentioning
confidence: 99%
“…The total number of patients who had fixated implants was 799 (76.02%) [11,12,15,16], and 252 patients (23.97%) had nonfixated implants [8,9,14,[17][18][19][20]. The number of implants based on implant site was 933 in the chin (81.05%) [9,12,[14][15][16][17][18][19][20], 160 in the malar region (13.90%) [8,16], and 58 (5.03%) as angle implants [11]. Follow-up periods ranged from one month to 17 years, except for two case series studies where follow-up periods were not reported [18,19].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation